Barriers to the Adoption of Digitalization in the Construction Industry: Perspectives of Owners, Consultants, and Contractors (Construction Economics and Building, 2023)
Construction organizations are moving toward adopting digitalization in response to Industry 4.0. However, the slow adoption of digitalization has been observed. This study aimed to assess the level of digitalization adoption and evaluate the barriers to adopting digitalization in the Jordanian construction industry by all project parties in the public and private sectors. The study targets were achieved through a structured questionnaire using SPSS software for analysis through the following statistical tests: Normality test, Mann-Whitney U, Kruskal-Wallis H, and Exploratory Factor Analysis (EFA). Most respondents used software at the design stage, and less than half did not use any software during the finishing stage. Regarding the barriers, twenty barriers to adopting digitalization were identified and grouped into five factors according to their importance: barriers related to the nature and system of the construction company, barriers related to the project parties, financial barriers, barriers related to system characteristics, and barriers related to construction project characteristics. Decision-makers should take the necessary measures to overcome such barriers depending on their importance. Previous studies have focused on the contractor's adoption of digitalization while neglecting other parties. This contributed to the full adoption of digitalization from the contractor side, with a noticeable delay from other project parties. This study focused on revealing the most critical barriers to adopting digitalization in the Jordanian construction industry from all project parties' perspectives based on their ranks. Furthermore, the study recommends effective strategies to overcome barriers as an update of past research.